The offer of native podcasts in Puerto Rico: the cultural identity of the independent sector in front of journalistic industry - Ortiz Díaz, Gabriela (2022)
Podcasting is torn between enabling participatory cultures thanks to the personal and cultural expression of independent podcasters, or being an industry promoted by the journalistic media and the “platform” of the communication market. The case of the sociocultural context of Puerto Rico also faces this issue, and it is of interest to identify the stable and regular offer of native podcasts made by the independent podcasting sectors and the journalistic industry. Based on the theories of participatory culture and the political economy of cultural industries, this research provides the first in-depth exploratory analysis of the podcast offer related to Puerto Rico based on a corpus or a sample of 815 podcasts according to data from the Observatory of Podcast of Puerto Rico. The quantitative content analysis methodology is applied to characterize these podcasts according to 11 variables: title / name, creator / user or media group / operator, own production for the network or not, theme, genre or narrative format, year of the start of production, number of episodes, average duration of the episodes, frequency of publication, authorship / presentation and hosting platform. The results show that independent podcasters are available in the user of 743 native podcasts (723 are amateurs and 20 are from journalistic media). Independent podcasts make up a space for cultural self-expression against mainstream culture. However, journalistic brands linked to the press such as El Nuevo Día, El Vocero and Metro Puerto Rico promote the native podcast of news. Anchor concentrates accommodation and favors cultural intermediation.